A study of double microring resonator behavior for 1.3 μm optical communication - Pornsuwancharoen, N.; Tasakorn, M.; Phromloungsri, R.; Yupapin, P. P. (My University, 2014)
A system that can be used to generate the new optical communication using a Gaussian pulse propagating within a nonlinear microring resonator double add/drop multiplexing system is discussed. By using the wide range of the Gaussian input pulses, for instance, when the input pulses of the common lasers with center wavelengths 1,300 nm are used. Achievements obtained have shown that very high capacity more than 300 channels for optical communication. © (2014) Trans Tech Publications, Switzerland.
Keywords: 1.3 μm communication; Add/Drop filter; Microring resonator